الاتساق النصي في مختارات من قصائد تميم البرغوثي - شيماء عزايزية (My University, 2026)
Summary: text linguistics view of texts was genral and comprehensive,studying many aspects of texts,such as coherens intentionality,acceptability,informativeness,and cohesion,which is another fundamental criterion for the existence of a text,cohesion deals with the formal structure of texts,linking structures to appear as a single,formally coherent unit this linkin relies on a set of tools established by halliday and ruqaiya hassan:reference,conjunction,ellipsis,and substition,these tools achieve grammatical cohesion,other tools,such as repetition and cohesion,achieve lexical cohesion ,thus cohesion branches into grammatical cohesion and lexical cohesion ,in the selected poms of the tamim al berghouthi,we find that reference and conjunction have significantly contributed to linking their verses,as have repetition and cohesion,which also worked effectively to achieve the cohesion of these poems,distinguished by their consistent external structure. -------------------- الملخص كانت نظرة لسانيات النص للنصوص نظرة عامة وشاملة،حيث عملت على دراسة جوانب عديدة في النصوص،كالانسجام،والقصد،والقبول،والتناص،والإعلامية،وكذلك الاتساق الذي يعدُّ هو الآخر من المعايير الأساسية التي يقوم عليها وجود النص،ويختص هذا الأخير بدراسة البنية الشكلية للنصوص،حيث يعمل على الربط بين التراكيب لكي تبدوا ككتلة واحدة متسقة شكليا،ويكون ذلك الربط بالاعتماد على مجموعة من الأدوات التي أقرها كل من هاليداي ورقية حسن وهي :الإحالة،الوصل،الحذف،والاستبدال،وهي أدوات تعمل على تحقيق الاتساق النحوي،وهناك أدوات أخرى مثل:التكرار والتضام التي تعمل على تحقيق الاتساق المعجمي،وعليه فإن الاتساق يتفرع إلى:اتساق نحوي واتساق معجمي.وفي تلك القصائد المختارة لتميم البرغوثي نجد أداتي الإحالة والوصل قد ساهما بشكل كبير في الربط بين أبياتها،وكذلك التكرار والتضام اللذين عملا كذلك بشكل فعال في تحقيق اتساق تلك القصائد،التي تميزت بفضل تلك الأدوات ببناءها الخارجي المتسق. -------------------- R¬¬¬êsumê: La linguistique textuelle adopte une approche gênêrale et exhaustive de textes,s intteressant a de nombreux aspects tels que la cohêrence. lîntentionnalitê. lâcceptabilitê.larichesse informative. Lîntertextualitê. Ainsi que la cohêsion. Critêre fondamental d êxistence du texte. Cette derniêre vise â etudier la structure formelle des textes et â relier les diffêrentes structures pour qu êlles forment un ensemble cohêrent. Ce lien est êtabli grâce â un ensemble dôutils validês par halliday et ruqayya hassan: la rêfêrence. La conjonction. La suppression et la substitution. Ces outils permettent dâtteindre la cohêsion grammaticale. Dautras outils. Comme la rêpêtition et la cohêsion. Permettent d atteindre la cohêsion lexicale. Ansi. La cohêsion se divise en cihêsion grammaticale et cohêsion lexicale. Dans ces poêmes choisis de tamim al-barghouthi. Nous constatons que les outils de rêfêrence et de conjonction ont grandement contribuê â lier ses vers. De même que la rêpêtition et lacohêsion. Qui ont êgalement fonctionnê efficacemment pour assurer la cohêsion de ces poêmes. Qui se distinguaient. Grâce â ces outils. Par leur structure externe rigoureuse.
Keywords: Text linguistics; cohesion; grammatical cohesion; lexicalcohesion; repetition; conjunction; reference; tamim al barghouti; لسانيات النص،الاتساق،الاتساق النحوي،الاتساق المعجمي،التكرار،التضام،الوصل،الإحالة،تميم البرغوثي.; Linguistiquetextuelle; cohesiongrammatical; cohesionlexical; conjonction; tamim al barghouthi